2019
DOI: 10.1371/journal.pone.0210247
|View full text |Cite
|
Sign up to set email alerts
|

Biological evaluation of isoflavonoids from Genista halacsyi using estrogen-target cells: Activities of glucosides compared to aglycones

Abstract: The purpose of this study was to evaluate the response of estrogen target cells to a series of isoflavone glucosides and aglycones from Genista halacsyi Heldr. The methanolic extract of aerial parts of this plant was processed using fast centrifugal partition chromatography, resulting in isolation of four archetypal isoflavones (genistein, daidzein, isoprunetin, 8-C-β-D-glucopyranosyl-genistein) and ten derivatives thereof. 7-O-β-D-glucopyranosyl-genistein and 7,4΄-di-O-β-D-glucopyranosyl-genistein were among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 78 publications
(108 reference statements)
0
14
0
Order By: Relevance
“…Having as reference standards the compounds isolated in our previous study of G. halacsyi [ 10 ], we confirmed the presence of two diglucosides of genistein [8- C ,4′- O -di-glucopyranosyl genistein ( 1 ) and 7,4′-di- O -glucopyranosyl genistein ( 2 )], five isoflavone monoglucosides [8- C -glucopyranosyl orobol ( 3 ), 7- O -glucopyranosyl isoprunetin ( 4 ), 8- C -glucopyranosyl 3′- O -methylorobol ( 5 ), 7- O -β- d -glucopyranosyl genistein ( 6 ), and 8- C -glucopyranosyl genistein ( 7 )], as well as seven isoflavonoid aglycones [daidzein ( 8 ), genistein ( 9 ), isoprunetin ( 10 ), 5- O -methylorobol ( 11 ), 8-methoxyformononetin ( 12 ), 3′-methoxyisoprunetin ( 13 ), and biochanin A ( 14 )] in some or all of the eight extracts ( Table 1 and Supplementary Material, Table S1 ). Of note, the isoflavonoids of Table 1 were previously isolated from a conventional MeOH extract of the aerial parts of G. halacsyi , using fast centrifugal partition chromatography followed by prep-TLC and/or silica and/or sephadex column chromatography of the fractions to deliver isolated compounds (>95% purity), as assessed by several spectrometric methods [ 10 ]. The data of Table 1 show that isoflavonoids 4 , 5 , 8 , 9 , 11 , 13 , and 14 were detected in all four Genista species, while 12 was not found in G. acanthoclada and G. hassertiana , 2 and 10 were not detected in G. depressa and G. millii, and 1 , 3 , 6 , and 7 were not observed in G. depressa .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Having as reference standards the compounds isolated in our previous study of G. halacsyi [ 10 ], we confirmed the presence of two diglucosides of genistein [8- C ,4′- O -di-glucopyranosyl genistein ( 1 ) and 7,4′-di- O -glucopyranosyl genistein ( 2 )], five isoflavone monoglucosides [8- C -glucopyranosyl orobol ( 3 ), 7- O -glucopyranosyl isoprunetin ( 4 ), 8- C -glucopyranosyl 3′- O -methylorobol ( 5 ), 7- O -β- d -glucopyranosyl genistein ( 6 ), and 8- C -glucopyranosyl genistein ( 7 )], as well as seven isoflavonoid aglycones [daidzein ( 8 ), genistein ( 9 ), isoprunetin ( 10 ), 5- O -methylorobol ( 11 ), 8-methoxyformononetin ( 12 ), 3′-methoxyisoprunetin ( 13 ), and biochanin A ( 14 )] in some or all of the eight extracts ( Table 1 and Supplementary Material, Table S1 ). Of note, the isoflavonoids of Table 1 were previously isolated from a conventional MeOH extract of the aerial parts of G. halacsyi , using fast centrifugal partition chromatography followed by prep-TLC and/or silica and/or sephadex column chromatography of the fractions to deliver isolated compounds (>95% purity), as assessed by several spectrometric methods [ 10 ]. The data of Table 1 show that isoflavonoids 4 , 5 , 8 , 9 , 11 , 13 , and 14 were detected in all four Genista species, while 12 was not found in G. acanthoclada and G. hassertiana , 2 and 10 were not detected in G. depressa and G. millii, and 1 , 3 , 6 , and 7 were not observed in G. depressa .…”
Section: Resultsmentioning
confidence: 99%
“…The data of Table 1 show that isoflavonoids 4 , 5 , 8 , 9 , 11 , 13 , and 14 were detected in all four Genista species, while 12 was not found in G. acanthoclada and G. hassertiana , 2 and 10 were not detected in G. depressa and G. millii, and 1 , 3 , 6 , and 7 were not observed in G. depressa . We have reported that 2 , 6 , and 7 , are the main constituents of the aerial parts of G. halacsyi [ 10 ]. The limited phytochemical compositions of the aerial parts of G. millii and, in particular, of G. depressa , with 2 missing from the first and 6 missing from both, compared to the respective compositions of G. acanthoclada and G. hassertiana are possibly related to the comparatively lower yields of the EtOAc extract of G. millii and the MeOH extract of G. depressa .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Docking plant-derived substances into ER and comparing their binding energies and interactions (above all hydrogen bonding) with those of estradiol is a common practice. Such studies deliver information on conformational flexibility [ 81 ], the ability of the investigated molecules to selectively modulate ERα/β ability [ 82 , 83 ], their possible reductive influence on breast cancer risk [ 84 ], or their applicability to reduce menopausal symptoms [ 85 ]. Most importantly, data derived in this way very often show good consistency with experiments [ 86 ].…”
Section: Application Of Molecular Modelling Methods In the Study Omentioning
confidence: 99%